1997
DOI: 10.1080/03610739708254283
|View full text |Cite
|
Sign up to set email alerts
|

Age Differences in Performance Awareness on a Complex Financial Decision-Making Task

Abstract: Individuals tend to be overconfident when making retrospective judgments about the quality of their decisions. However, few studies have focused on age differences in estimates of decision quality. In the present experiment performance estimates were provided by task-trained and untrained young and old individuals following completion of a series of complex financial decisions. Confidence levels were assessed by examining discrepancies between perceived and actual solution quality. Performance estimates of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 16 publications
0
23
0
2
Order By: Relevance
“…Other papers that have resulted from this study include an analysis of participants' metacognitive performance (Hershey & Wilson, 1997), and an analysis of age-differences in information search (Walsh & Hershey, 1993; experiment 2).…”
Section: Notesmentioning
confidence: 98%
“…Other papers that have resulted from this study include an analysis of participants' metacognitive performance (Hershey & Wilson, 1997), and an analysis of age-differences in information search (Walsh & Hershey, 1993; experiment 2).…”
Section: Notesmentioning
confidence: 98%
“…According to [32], self is "the totality of a person's feelings about himself to serve as an object". It was like turning a person (the self) and the actual assessment that he (she) is who and what is what [33].…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…They showed that elderly people were more accurate than young people in predicting the accuracy of their judgments. Hershey and Wilson (1997) studied performance awareness on a complex financial-decision task. They showed that ''the absolute magnitude of errors made by older participants were equivalent to those made by younger ones' ' (p. 268).…”
Section: Aging and Probabilistic Learning In Single-and Multiple-cue mentioning
confidence: 99%